2005
DOI: 10.1385/cbb:43:2:289
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Diabetic Complications

Abstract: The morbidity and mortality associated with diabetes is the result of the myriad complications related to the disease. One of the most explored hypotheses to explain the onset of complications is a hyperglycemia-induced increase in oxidative stress. Reactive oxygen species (ROS) are produced by oxidative phosphorylation, nicotinamide adenine dinucleotide phosphate oxidase (NADPH), xanthine oxidase, the uncoupling of lipoxygenases, cytochrome P450 monooxygenases, and glucose autoxidation. Once formed, ROS deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
220
0
19

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(244 citation statements)
references
References 376 publications
5
220
0
19
Order By: Relevance
“…A consistently high oxidative stress level or low antioxidant defence were revealed in patients with diabetes, which are responsible for many pathogenic processes of diabetic complications. 228 As for some other pathologies, a general protective function of Se may rely on the action of Se-proteins for ROS reduction. Several studies demonstrated that Se prevents or alleviates the adverse effects that diabetes has on cardiac and renal functions, vascular complications, and atherosclerosis progression.…”
Section: Diabetesmentioning
confidence: 99%
“…A consistently high oxidative stress level or low antioxidant defence were revealed in patients with diabetes, which are responsible for many pathogenic processes of diabetic complications. 228 As for some other pathologies, a general protective function of Se may rely on the action of Se-proteins for ROS reduction. Several studies demonstrated that Se prevents or alleviates the adverse effects that diabetes has on cardiac and renal functions, vascular complications, and atherosclerosis progression.…”
Section: Diabetesmentioning
confidence: 99%
“…Oxidative stress plays an important role in the development of DR [119]. In this regard, it was investigated whether polymorphisms in the glutathione S-transferases M1 (GSTM1) and T1 (GSTT1) genes, encoding enzymes with a role in repairing endogenous compounds affected by oxidative stress, are associated with DR. A casecontrol study including 604 Caucasians with T2D…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…O 2˙ˉ can react with nitroxide (NO˙, hereafter NO) and form strong oxidant peroxinitrite (ONOOˉ). These processes result in acute endothelium dysfunctions and activation of inflam-matory processes in blood vessels of patients with DM and they are the factors contributing to development of diabetic complications (Niedowicz and Daleke 2005;Cerielo 2006;Shahab 2006). The most known complications are cardiovascular diseases, impairment of vascular system (Liptáková 1999;Jay et al 2006), peripheral nerves, kidneys, epidermis, retina, lens, neurodegenerative diseases like Alzheimer or Parkinson diseases and others (El-Atat et al 2004;Vasavada and Agarwal 2005).…”
mentioning
confidence: 99%